DETERMINATION ENTREPRENEURIAL STRATEGIES, MARKETING STRATEGIES AND ENTREPRENEURIAL OPPORTUNITIES FOR THE BUSINESS SUCCESS IN THE ERA OF DISRUPTION - Djoko Setyo Widodo (Dinasti International Journal of Education Management And Social Science, 2021)
The literature review article Determining Entrepreneurial Strategy, Marketing Strategy and Entrepreneurial Opportunity for Business Success in the Era of Disruption is a scientific article that aims to build a research hypothesis on the influence between variables that it will used in further research within the scope of Human Resource Management. The method of writing literature review articles is the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other academic online media. The results of this Literature Review article are: 1) Entrepreneurial Strategy determines Business Success in the Era of Disruption; 2) Marketing Strategy determines Business Success in the Era of Disruption; and 3) Entrepreneurial Opportunities determine Business Success in the Era of Disruption. Apart from these three exogenous variables that affect the endogenous variables of Business Success in the Era of Disruption, there are still many other factors, including the Work Environment, Communication, Promotion, Sales, and Work Culture.